Gender Disparity in Completing School Education in India over Regions - Husain, Zakir (Journal of Research in Educational Sciences; Vol 1 No 2 (2010): JRES, Volume I, Issue 2(2), Winter 2010, 2010)
Is gender disparity in education greater in North India? This paper seeks to answer this question by examining gender differences in probability of completing school education across regions in India. A Gender Disparity Index is calculated using National Sample Survey Organization unit level data from the 61st Round and regional variations in this index analyzed to examine the hypothesis that gender disparity is greater in the North, comparative to the rest of India. This is followed by an econometric exercise using a logit model to confirm the results of the descriptive analysis after controlling for socio-economic correlates of completing school education. Finally, the Fairlie decomposition method is used to estimate the contribution of explanatory variables in explaining differences in probabilities of completing schooling across regions. The results reveal that gender disparities are greater in North India, for total and rural population, and in Eastern India, for urban population. However, the ‘residual effect’ after accounting for effect of explanatory variables - often referred to as ‘discrimination effect’, as opposed to disparity – is higher in Eastern India, irrespective of the place of residence.